Eosinophils are an insignificant cellular component of rheumatoid synovium in patients with late stage disease: comparative distributions with mast cells and macrophages. - Tetlow, L C (1996)
OBJECTIVES: To examine the distribution of eosinophils in rheumatoid synovial tissue and to determine whether or not their tissue distribution is related to that of mast cells or macrophages. METHODS: Consecutive tissue sections from 31 specimens of rheumatoid synovial tissue and cartilage-pannus junction were stained for eosinophils, mast cells, and macrophages with monoclonal antibodies and immunolocalisation techniques. RESULTS: Eosinophils were absent in 28 of the 31 specimens; the remaining three showed only the occasional eosinophil. By contrast the mean values for mast cell and macrophage (CD68/KP1 marker) distributions were 24 (SD 22) and 104 (SD 66) per mm2, respectively. CONCLUSION: There are very few eosinophils in inflamed rheumatoid synovial tissue and sites of cartilage erosion despite the presence of appreciable numbers of macrophages and mast cells, the mast cells showing various states of activation. Such findings are at variance with those in allergic inflammation, in which the presence of eosinophils has been reported to be regulated by specific chemokines and adhesion molecules.